Biocultural homogenization: Exotism of the femenine landscape of Latin America Homogeneización biocultural: Exotización del paisaje Femenino Latinoamericano - Castellanos, Angelina Paredes; Rozzi Marin, Ricardo Roberto (My University, 2018)
The colonial language "of the Imperial Eye" on Latin America is summarized in an "Exotic Myth about the landscape", which today is combined with the occidental globalization at its ecological crossroads. Latin America is a key hermeneutic sign of analysis, because exposes the aesthetic ideological root that accompanies this uniformity of the landscape with a single objective semantics based on an exotist ideology. The aesthetic side that stands out in the question of the nature of "exotic America" reveals the importance of valuing an alternative, ecological, aesthetic and post-modern-exotic hermeneutic to re-think the new Earth or the New World, America. Ancestrally and until today called Pachamama in the southern Andes. El lenguaje colonial "del ojo imperial" sobre América Latina se resume en un mito exótico sobre el paisaje, que hoy se conjuga con la globalización Occidental en su encrucijada ecológica. América Latina es un signo hermenéutico clave de análisis, debido a que expone la raíz ideológica estética que acompaña a la uniformización del paisaje con una sola semántica objetiva basada en una ideología exotista. El lado estético que resalta en la pregunta por la naturaleza de la "América exótica" revela la importancia de valorar una hermenéutica alternativa, ecológica, estética y post-exótica para re-pensar la Tierra Nueva o el Nuevo Mundo, América. Ancestralmente y, hasta hoy llamada, Pachamama en los Andes del sur.
Keywords: américa latina; ecology; ecología; exoticism; exotismo; feminine geography; geografía femenina; latin america